2011
DOI: 10.1179/2042618611y.0000000004
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic ankle pain using joint mobilization and ASTYM® treatment: a case report

Abstract: Treatment of ankle sprains predominately focuses on the acute management of this condition; less emphasis is placed on the treatment of ankle sprains in the chronic phase of recovery. Manual therapy, in the form of joint mobilization and manipulation, has been shown to be effective in the management of this condition, but the combination of joint mobilization and manipulation in tandem with ASTYMH treatment has not been explored. The purpose of this case report is to chronicle the management of a patient with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
0
16
1
Order By: Relevance
“…19 The treatment includes specific protocols and instruments used to stimulate affected soft tissues to heal and regenerate at a cellular level. 20 ASTYM has been shown to cause increased fibroblast recruitment and activation in rat tendons which should theoretically promote proper healing, but this has not been thoroughly studied in humans. [21][22][23] ASTYM treatment is thought to activate a regenerative response in soft tissues via induction of leakage from dysfunctional capillaries which leads to fibroblast activation, macrophage mediated phagocytosis, and a local release of growth factors.…”
Section: 13mentioning
confidence: 99%
See 1 more Smart Citation
“…19 The treatment includes specific protocols and instruments used to stimulate affected soft tissues to heal and regenerate at a cellular level. 20 ASTYM has been shown to cause increased fibroblast recruitment and activation in rat tendons which should theoretically promote proper healing, but this has not been thoroughly studied in humans. [21][22][23] ASTYM treatment is thought to activate a regenerative response in soft tissues via induction of leakage from dysfunctional capillaries which leads to fibroblast activation, macrophage mediated phagocytosis, and a local release of growth factors.…”
Section: 13mentioning
confidence: 99%
“…[21][22][23] ASTYM treatment is thought to activate a regenerative response in soft tissues via induction of leakage from dysfunctional capillaries which leads to fibroblast activation, macrophage mediated phagocytosis, and a local release of growth factors. [20][21][22][23][24] While eccentric exercise and ASTYM should theoretically be useful in the management of HHT, the research supporting both of these interventions is lacking and there are no studies that have reported the effects of a combined treatment approach. Therefore, the purpose of this report was to present the management and outcomes of a patient with bilateral HHT who was treated with eccentric exercise and ASTYM.…”
Section: 13mentioning
confidence: 99%
“…12,13 Astym therapy has been shown to increase movement and decrease pain in patients with inappropriate fibrosis and in patients with other soft tissue dysfunctions. 6,[9][10][11] Davies and Brockopp, 14 in a previous pilot study, demonstrated that Astym therapy increased active range of motion (AROM) of shoulder flexion and abduction, and improved Disabilities of the Arm, Shoulder, and Hand Outcome Measure (DASH) scores in patients with scar tissue around their mastectomy incision, drain site, and axilla. 14 The same study also reported that 56% of women were unable to wear a bra before Astym treatment, suggesting hypersensitivity of scars and clothing restrictions that affect BCSs.…”
Section: Astymmentioning
confidence: 99%
“…7,8 It has also been found to reduce pain and increase function in people with soft tissue dysfunction. 6,[9][10][11] The aim of Astym treatment is to engage the regenerative mechanisms of the body in order to resorb scar tissue, stimulate tissue turnover, and regenerate soft tissues. 6 Handheld instrumentation is applied topically to locate underlying dysfunctional soft tissue and then transfer particular pressures and shear forces to the dysfunctional tissue through specific protocols and patterns developed from scientific and clinical study.…”
Section: Astymmentioning
confidence: 99%
“…11 Clinical studies support the effectiveness of Astym therapy in the treatment of various soft tissue dysfunctions. [11][12][13][14][15] However, no publications have specifically addressed Astym therapy's role in knee stiffness following TKA. Thus, we aimed to evaluate (1) ROM and (2) subjective functional improvements in post-TKA patients who suffered from stiffness recalcitrant to other nonoperative modalities, who underwent Astym therapy after failure of conventional therapy.…”
mentioning
confidence: 99%